Diagram Vektor Arus dan Tegangan Saluran Transmisi - Margunadi Margunadi (Journal of Mathematical and Fundamental Sciences, 1965)
Ichtisar. Untuk saluran2 transmisi pendek untuk membuat suatu diagram vector jang menjatakan hubungan antara tegangan dan arus daripada udjung awal dan udjung achir, adalah suatu hal jang sederhana. Untuk saluran listrik jang pandjang prosedur ini adalah rumit, karena adanja kapasitansi2 shunt jang didistribusikan. Akan tetapi dengan merubah persamaan2 untuk saluran pandjang, hal ini dapat dilakukan dengan tjara relatif praktis. Untuk maksud itu, bagi tiap besaran dipakailah harga2 per unit berdasarkan tegangan pada udjung achir dan arus beban karakteristik. Suatu lingkaran, sebagai locus daripada tegangan awal sesuai dengan factor daja = 1, djuga diturunkan dari uraian itu. Abstract. For short transmission lines it is a simple matter to construct a vector diagram showing the phase relationships between the sending-end and receiving-end voltages and currents. For an electrically long line the procedure is complicated because of the presence  of the distributes shunt capacitances. By transforming the equations of a long line, however, it is possible to accomplish this in a relatively practical way. For that purpose per unit  quantities are used  with the receiving-end voltage and the surge-impedance-load current taken as basis. A circle as locus of sending-end voltage corresponding to unity sending "“end power factor  is also derived from the consideration.